THE PROBLEM OF STERILITY IN UKRAINE: THE ROLE OF SUPPORTING REPRODUCTIVE TECHNOLOGIES AND RUNNING OF PREGNANCY IN WOMEN WITH LASTING CURED STERILITY. - Бойчук, О. Г.; Макарчук, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The problem of sterility of married couples is actual not only from medical, medico-genetic side, but also in social, biological and psychological aspect. Men and women’s factors with practically the same frequency may become the reason of sterile marriage and in great amount of couples these factors are combined. Low effectiveness of natural fertility recovery stimulated the development of supporting reproductive technologies. The wide use of supporting reproductive technologies which determine induction of ovulation as well as frequent successful use of modern ovulation stimulations at treating endocrine forms pf sterility leads to the rise of inductive pregnancies for the last few years, and the problem of such pregnancies preserving and giving birth to healthy children has become extremely important and actual. The article reveals the analysis of literary reviews that identify about significant peculiarities of pregnancy running, delivery and after delivery period in women after supporting reproductive technologies, that is: premature birth, loss of pregnancy, multi foetuses, obstetric complications. Taking into account the rise of pregnancies quantity which occurred after extra corporal fecundation, at the given period the further development of tactics of pregnancy, delivery and after delivery period is necessary for the given category of women with the aim to reduce reproductive losses.